Strategi Peningkatan Daya Saing Melalui Inisiasi Pemasaran Kolektif Produk Hortikultura di Kapanewon Patuk - Risma Yulianti yulianti; Siti Nurlaela; Elea Nur Aziza (Greenation Publisher & Yayasan Global Research National, 2026)
The horticulture sector has significant economic potential; however, farmers continue to face several constraints in improving competitiveness, particularly farm fragmentation, weak bargaining power, limited access to market information, and the absence of product quality standardization. This study aims to analyze the initiation process of collective marketing for horticultural products, identify internal and external factors affecting its development, and formulate strategic priorities to enhance farmers’ competitiveness. This research employed a descriptive qualitative approach, with data collected through observation, in-depth interviews, documentation, and Focus Group Discussion (FGD). The informants consisted of four horticultural farmers as key informants and two additional informants, namely an agricultural extension officer and a collection point manager. Data were analyzed using IFAS and EFAS matrices, SWOT analysis, and the Quantitative Strategic Planning Matrix (QSPM). The results indicate that the initiation of collective marketing in Patuk District remains at the stage of awareness building and informal coordination through WhatsApp. Social capital in the form of trust, solidarity, and information openness has been established, but it has not yet been supported by adequate institutional structure, administration, quality standardization, and production continuity. The IFAS and EFAS results positioned the strategy in Quadrant III, with an X value of -0.89 and a Y value of 1.15, indicating that the recommended strategy is the WO strategy. Based on QSPM analysis, the strategic priorities are the formulation and implementation of cultivation standard operating procedures, digitalization of group administration and financial records, strengthening institutional governance through collaboration with BPP Patuk, and optimizing WhatsApp-based coordination. These strategies are expected to strengthen farmer institutions and sustainably improve the competitiveness of horticultural products.